2021
DOI: 10.1101/2021.02.15.431332
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamin is primed at endocytic sites for ultrafast endocytosis

Abstract: Dynamin mediates fission of vesicles from the plasma membrane during endocytosis. Typically, dynamin is recruited from the cytosol to endocytic sites, requiring seconds to tens of seconds. However, ultrafast endocytosis in neurons internalizes vesicles as quickly as 50 ms during synaptic vesicle recycling. Here we demonstrate that Dynamin 1 is pre-recruited to endocytic sites for ultrafast endocytosis. Specifically, Dynamin 1xA, a splice variant of Dynamin 1, interacts with Syndapin 1 to form molecular condens… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 102 publications
(160 reference statements)
3
31
0
Order By: Relevance
“…The phosphomimetic form of Dyn1xA cannot form liquid-like droplets and is diffuse throughout the cytoplasm similar to Syndapin 1 knock down phenotype which slows down ultrafast endocytosis in previous study (Imoto et al, 2021). Together, these results suggest that the liquid-like properties of Dyn1xA and Syndapin 1 are important for ultrafast endocytosis.…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…The phosphomimetic form of Dyn1xA cannot form liquid-like droplets and is diffuse throughout the cytoplasm similar to Syndapin 1 knock down phenotype which slows down ultrafast endocytosis in previous study (Imoto et al, 2021). Together, these results suggest that the liquid-like properties of Dyn1xA and Syndapin 1 are important for ultrafast endocytosis.…”
Section: Introductionsupporting
confidence: 72%
“…To examine the requirement for dephosphorylation, we localized wild-type, phosphomimetic (S774/778D), and phospho-deficient (S774/778A) forms of Dyn1xA in neurons. We visualized Dyn1xA-GFP along with an active zone protein, Bassoon, using Stimulated Emission Depletion (STED) microscopy (Figure 2K (Imoto et al, 2021), most Dyn1xA signals were found within 100 nm from the active zone edge where ultrafast endocytosis takes place (Watanabe et al, 2013a). Likewise, phosphodeficient Dyn1xA accumulated within 100 nm from the active zone edge.…”
Section: Phase Separation Of Dyn1xa At Synapses Requires Dephosphoryl...mentioning
confidence: 99%
See 2 more Smart Citations
“…We first examined SDPN-1/syndapin 1, a protein known to play important roles in early stages of membrane invagination during both activity-dependent bulk endocytosis (ADBE) 89,90 and ultrafast endocytosis 91 . We reasoned that if ATG-9…”
Section: Ap-1 Adaptor Complexmentioning
confidence: 99%